Knowledge and attitude of Bangladeshi dentists towards Conebeam computed tomography (CBCT) (Bangladesh Journal of Medical Science, 2025)
Background Despite potential benefits of CBCT, the utilization of CBCT in dental practices is influenced by various factors, including awareness, knowledge, attitudes, and barriers among dentists. This study aimed to assess the awareness, knowledge, attitudes, and barriers regarding CBCT utilization among Bangladeshi dentists. Material and Methods A cross-sectional survey was conducted among 500 dentists practicing in Bangladesh. The survey questionnaire comprised items assessing demographic information, awareness of CBCT, attitudes towards its utility, perceived barriers, and preferences for continuing education. Data were analyzed descriptively, and statistical tests such as chi-square and logistic regression were employed to identify significant predictors of positive attitudes towards CBCT. Results The majority of respondents demonstrated a high level of awareness regarding CBCT (80%), with positive attitudes towards its utility in various clinical scenarios. However, practical utilization remained limited, primarily due to barriers such as high costs, limited accessibility, and interpretation challenges. Dentists expressed a strong interest in continuing education related to CBCT. Conclusion There is a high level of awareness and positive attitudes towards CBCT, significant barriers hinder its widespread adoption. Addressing these barriers can enhance the utilization of CBCT in dental practices, ultimately improving patient outcomes and advancing dental care in Bangladesh.Bangladesh Journal of Medical Science Vol. 24 No. 02 April’25 Page : 457-464